Perbandingan Kadar Aspal JMF dan Lapangan Melalui Pengujian Ekstraksi Metode Reflux Campuran AC-WC - Efri Yulianti Rete; Alpius; Herman Welem Tanje (Paulus Civil Engineering Journal, 2025)
Asphalt content refers to the weight percentage of asphalt contained in an asphalt concrete mix or asphalt mixture for road construction. Asphalt is a binding material used in road construction to provide strength and durability against loads, as well as to protect the road surface from damage due to environmental factors such as water, heat, and traffic loads. The asphalt content in the asphalt mixture plays an important role in determining the physical and mechanical properties of the mixture. The right amount of asphalt must be used to achieve a mixture that has adequate strength, resistance to deformation, and resistance to cracking. If the asphalt content is too low, the mixture may become brittle and susceptible to cracking. Conversely, if the asphalt content is too high, the mixture can become soft and susceptible to plastic deformation. The purpose of the research is to determine the comparison of asphalt content in the field and the Job Mix Formula. Asphalt content can be measured by examining the extraction results using specific methods, such as the asphalt extraction test. Extraction testing is performed using the reflux extraction method to determine the asphalt content. This process is generally carried out on asphalt and aggregate mixtures used in road construction. According to the 2018 General Specifications revision 2, the tolerance limit for asphalt content is ± 0.3% of the mixture weight.